Global Glacier Mass Loss During the GRACE Satellite Mission (2002-2016) - Wouters, Bert; Gardner, Alex S.; Moholdt, Geir (Frontiers in Earth Science, 2019)
Glaciers outside of the ice sheets are known to be important contributors to sea level rise. In this work, we provide an overview of changes in the mass of the world's glaciers, excluding those in Greenland and Antarctica, between 2002 and 2016, based on satellite gravimetry observations of the Gravity Recovery and Climate Experiment (GRACE). We find that over this 14-yr period, glaciers lost about 3000 Gigatonnes of mass, equivalent a sea level contribution of 8 mm. We present annual mass balances for 17 individual glaciers regions, that show a qualitatively good agreement with published estimates from in situ observations. We find that annual mass balance varies considerably from year to year, which can in part be attributed to changes in the large-scale circulation of the atmosphere. These variations, combined with the relatively short observational record, hamper the detection of acceleration of glacier mass loss. Our study highlights the need for continued observations of the Earth’s glacierized regions.